2018
DOI: 10.1093/migration/mny013
|View full text |Cite
|
Sign up to set email alerts
|

Young Somalis’ social identity in Sweden and Britain: The interplay of group dynamics, socio-political environments, and transnational ties in social identification processes

Abstract: In this article, we aim to contribute to the literature on social identification among migrants and minorities by offering a theoretical framework that accounts for the interplay of socio-psychological factors, local and transnational group dynamics, and the socio-political environment in which migrants live. This approach enables us to analyse not only the political significance of identity, but also the psychology of identity formation. Drawing upon qualitative data, we analyse how young Somalis (N = 43) liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…First-generation Somalian youth in Sweden have been found to report feelings of social exclusion and difficulties in inclusion. Many of these issues were linked to the direct experience of migration; however, similar issues were found in other studies comparing Somalis in the UK and Sweden (Scuzzarello and Carlson 2019). Several studies have reinforced previous findings that hyphenated identities are less actualized in Sweden.…”
Section: Somalians Turks Vietnamese and Poles In Swedensupporting
confidence: 58%
See 1 more Smart Citation
“…First-generation Somalian youth in Sweden have been found to report feelings of social exclusion and difficulties in inclusion. Many of these issues were linked to the direct experience of migration; however, similar issues were found in other studies comparing Somalis in the UK and Sweden (Scuzzarello and Carlson 2019). Several studies have reinforced previous findings that hyphenated identities are less actualized in Sweden.…”
Section: Somalians Turks Vietnamese and Poles In Swedensupporting
confidence: 58%
“…For example, in Osman et al (2020), participants corrected an earlier version of the article draft where they were referred to as 'Somali-Swedish adolescents', affirming that they would rather be referred to as 'Somali' despite living in Sweden. Other previous research has highlighted that for individuals with Somali backgrounds in Sweden, identification becomes binary; one is a Somali in Sweden and a Swede in Somalia (Scuzzarello and Carlson 2019). This is common finding within studies of ethnic identity (see Verkuyten 2018 for a review).…”
Section: Somalians Turks Vietnamese and Poles In Swedenmentioning
confidence: 78%
“…Especially so in a context like Sweden, where racial and ethnic groups are not clearly defined, and where there is no direct language for group identifications (Svensson & Syed, 2019). Apart from the word race not being used in the Swedish vocabulary, there is also largely a lack of accepted hyphenated identities (e.g., Asian‐American), which may increase the feelings of marginalization and otherness (Scuzzarello & Carlson, 2018; Svensson & Syed, 2019). Moreover, there has been a visible increase in the normalization of prejudice and racism throughout the country (Hellström & Nilsson, 2010; Iakimova, 2018; Schierup, Ålund, & Neergaard, 2018).…”
Section: Discrimination and Ethnic Discrimination In Swedenmentioning
confidence: 99%
“…A major protective factor against the negative consequences associated with discrimination is a sense of ethnic belonging (e.g., Pascoe & Richman, 2009; Rivas‐Drake et al., 2014). However, recent research has suggested that many young people in Sweden have difficulties in developing a positive sense of ethnic group identification (Gyberg et al., 2018; Scuzzarello & Carlson, 2018; Svensson, Berne, & Syed, 2018), due to a dichotomous division of “Swede” versus “ immigrant” (Almqvist, 2006; Gyberg et al., 2018; Johansson & Olofsson, 2011; Scuzzarello & Carlson, 2018; Svensson et al., 2018). Group identification can be understood in both objective and subjective terms (Syed, Juang, & Svensson, 2018), where objective measures are researcher driven assignments (i.e., immigrant background) while subjective measures allow people to define their own in‐groups (i.e., self‐defined ethnicity).…”
Section: Discrimination and Ethnic Discrimination In Swedenmentioning
confidence: 99%
“…Danish Somalis show characteristics similar to those in the rest of Scandinavia (Horst, 2018;Scuzzarello & Carlson, 2019) which differ, in turn, from diasporas in Anglosaxon countries (Abdulle, 2018;Chambers, 2017;Liberatore, 2018). One of them is their higher level of acculturation.…”
Section: The Somali Conflict and The Somali Diaspora In Denmarkmentioning
confidence: 94%